Intra-articular injection of bone marrow aspirate concentrate (BMAC) or adipose-derived stem cells (ADSCs) for knee osteoarthritis: a prospective comparative clinical trial - Andrea Pintore; Donato Notarfrancesco; Arnaldo Zara; Antonio Oliviero; Filippo Migliorini; Francesco Oliva; Nicola Maffulli (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background We determined whether autologous mesenchymal stem cells (MSCs) injections provide clinical and functional improvements in knee osteoarthritis (KOA) patients, and whether the results differ between autologous bone marrow cells (BMAC) and adipose-derived stromal cells (ADSCs). Methods Between January 2021 and April 2022, 51 patients undergoing intra-articular injection of BMAC and 51 patients undergoing intra-articular injection of ADSCs were prospectively recruited. The Kellgren and Lawrence (K–L) classification was used to grade the severity of osteoarthritis. Knee Injury and Osteoarthritis Outcome Score (KOOS), Oxford Knee Score (OKS), and visual analog scale (VAS) were collected for all 102 patients in the previous week before the procedures, and at the one and 6 months from injection. Results Knee KOOS scores, knee OKS scores, and VAS pain scores changed in similar ways in the two treatment groups. Both treatment groups demonstrated significant improvement pre-procedure to post-procedure in knee KOOS scores (p < 0.0001), knee OKS scores (p < 0.0001), and VAS pain scores (p < 0.0001). Patients with K–L grade 2 showed better functional and clinical outcomes than patients with K–L grades 3 and 4 (p < 0.0001). Conclusion Both intra-articular BMAC and ADSC injections significantly improved pain and functional outcomes at 6-month follow-up in patients with KOA. The difference between BMAC and ADCSs groups as tissue sources of MSCs was not statistically significant in terms of clinical and functional outcomes.